2015
DOI: 10.1016/j.neuroimage.2015.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intrinsic motivation on feedback processing during learning

Abstract: Learning commonly requires feedback about the consequences of one’s actions, which can drive learners to modify their behavior. Motivation may determine how sensitive an individual might be to such feedback, particularly in educational contexts where some students value academic achievement more than others. Thus, motivation for a task might influence the value placed on performance feedback and how effectively it is used to improve learning. To investigate the interplay between intrinsic motivation and feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 39 publications
6
62
0
5
Order By: Relevance
“…However, when external incentives and punishments no longer exist, and an individual participates in an activity in an autonomous manner, it was found that one's dopaminergic value system still responds to informational feedback (Di Domenico and Ryan, 2017;Reeve and Lee, 2019). As a likely origin of RewP suggested by researchers (Tricomi et al, 2006;Depasque and Tricomi, 2015), the anterior striatum is deeply involved in reward processing and feedback evaluation. Thus, in a pioneering and influential functional magnetic resonance imaging (fMRI) study, Murayama et al (2010) tracked activity in the anterior stratum and used it to measure one's autonomous motivation when performance-based rewards were not provided.…”
Section: Introductionmentioning
confidence: 99%
“…However, when external incentives and punishments no longer exist, and an individual participates in an activity in an autonomous manner, it was found that one's dopaminergic value system still responds to informational feedback (Di Domenico and Ryan, 2017;Reeve and Lee, 2019). As a likely origin of RewP suggested by researchers (Tricomi et al, 2006;Depasque and Tricomi, 2015), the anterior striatum is deeply involved in reward processing and feedback evaluation. Thus, in a pioneering and influential functional magnetic resonance imaging (fMRI) study, Murayama et al (2010) tracked activity in the anterior stratum and used it to measure one's autonomous motivation when performance-based rewards were not provided.…”
Section: Introductionmentioning
confidence: 99%
“…42 A study using functional magnetic resonance imaging discovered that motivation may modulate neural responses to performance-related feedback and, furthermore, that changes in motivation facilitate processing in areas that support learning and memory. 43 Although goal orientation 44,45 and feedback seeking 38,46 frameworks are very relevant to our findings, our inquiry focused primarily on the process rather than on the participants. This limited our ability to explore the fit of our data to these frameworks.…”
Section: Discussionmentioning
confidence: 97%
“…A study using functional magnetic resonance imaging discovered that motivation may modulate neural responses to performance‐related feedback and, furthermore, that changes in motivation facilitate processing in areas that support learning and memory …”
Section: Discussionmentioning
confidence: 99%
“…Donald contains three important elements, namely; (1) Motivation starts from the energy change in the person, (2) Motivation is characterized by feelings of affective arousal, (3) Motivation marked by reactions to achieve the goal (Vibulphol, 2016;Lee, 2010). Learning motivation can arise because of intrinsic factors and extrinsic factors, where in the learning process teaching intrinsic motivation and extrinsic motivation is needed as a driver of self to advance and improve the failure (Feng, Fan & Yang, 2013;Awad, Al-Haqan & Moreau, 2017;DePasque & Tricomi, 2015;Sengodan & Iksan, 2012). Based on the background that has been described, the hypothesis of this study are: H 01: No positivity effect and significant influence from classroom climate variables towards learning outcomes in productive subjects.…”
mentioning
confidence: 98%